Low-energy hydrogen uptake by small-cage Cn and Cn-1B fullerenes. (August 2018) - Dominguez-Gutierrez, F. Javier; Krstic, Predrag S.; Irle, Stephan; Cabrera-Trujillo, Remigio
Abstract: We present a theoretical study of the hydrogen uptake capability of carbon fullerene cages Cn and their boron-doped heterofullerene equivalents Cn-1 B, with n = 20, 40, and 60, irradiated by hydrogen atoms in an impact energy range of 0.1–100 eV. In order to predict exohedral and endohedral hydrogen captures as well as the scattering probability of hydrogen for various cage types and sizes, we perform quantum-classical molecular dynamics (QCMD) calculations using the self-consistent-charge density-functional tight-binding (SCC-DFTB) method. Maximum endohedral hydrogen capture probabilities of 20% for n = 60 and 14% for n = 40 are found at impact energies close to 15 eV for both Cn and Cn-1 B systems. For n = 20, however, endohedral capture is observed at a maximum of 2%, while the exohedral capture reaches a maximum of 5% both at 15 eV. Similar results for the hydrogen capture are obtained by classical molecular dynamics based on the ReaxFF potential. Finally, the stopping cross section per carbon atom from the QCMD simulations for all cage sizes displays a linear dependence on the projectile velocity with a threshold at 0.8 eV, and extrapolates well to the available theoretical data. Graphical abstract: